Analisis Keefektifan Sistem Pembelajaran Klasikal Di RBQ Daniel Family Durrotul Qur’an Kota Lubuk Linggau - Lusia, Yuyun Cahyani; Kamsi, Nurlila; Dinanti, Riska Destri (Edification Journal : Pendidikan Agama Islam, 2025)
The RBQ Daniel Family Durrotul Quran is one of the non-formal educational establishments in Lubuklinggau that teaches the Quran. This establishment provides a venue for adults and children to study the Quran. The Qur'an is taught at this institution utilizing a traditional learning approach, in which the teacher presents the same content to the class at the same time. The purpose of this study is to determine the efficacy of classical learning at RBQ Daniel Family Durrotul Qur'an as well as its methodology. This study employs a qualitative approach. The study's findings suggest that RBQ Durrotul Quran's traditional teaching method is highly successful. Due to the simultaneous supply of information, recitation, and memorizing, classical learning can save time. Minor problems do exist, though, such as pupils talking and playing while the teacher is explaining the content, which causes the teachers to remind the students to pay attention to what they are being taught.